P111 A user centred approach to the design of point-of-care and self-test mobile phone diagnostics for sexually transmitted infections (STIs). (23rd May 2012) - Voula, G; Balachandran, W; Lowndes, C; Howell-Jones, R; Aicken, C R; Mercer, C H; Sutcliffe, L; Sonnenberg, P; Jackson, M; Estcourt, C S; Sadiq, S T; Hone, K
Abstract : Background: Control of STIs in vulnerable populations is difficult because of inadequate access to prompt diagnosis and treatment and may be enhanced by better community based STI surveillance. The high rates of mobile and smart phone use in these populations and the development of novel personalised diagnostic technologies which theoretically enable highly accurate self-testing diagnostics for STIs that can be electronically linked to clinical care pathways and STI data capture, may help address these challenges. A major challenge for these systems is the development of clinically relevant and acceptable Human Technology Interfaces (HTIs) for Mobile-Web Applications. Objectives: To describe a methodological approach to develop a mobile phone/web-based management system that can link rapid self-test diagnostics to clinical care pathways and community based surveillance. Methods: We adopt a user centred approach to the development of a HTI for self-managing STI diagnosis with initial exploratory pilot studies to gather functional, user and clinical requirements of the HTI. Iterative development of functional prototypes exploring design possibilities and technology features is followed by the formative evaluation of interface design alternatives through qualitative and controlled usability studies with target users and existing surveillance capture mechanisms. Results: A user centred, multi-disciplinary approach allows for successful capture and integration of social science methods to inform functional requirements for an effective and user acceptable mobile and web-based self-managing STI diagnostics and surveillance system. Discussion: Future testing in simple and complex, community based studies are needed to primarily assess safety and then effectiveness for improving access to care, enhanced partner notification and development of community based capture of surveillance data.